Health economic modelling of diabetic kidney disease in patients with type 2 diabetes treated with Canagliflozin in Belgium. Issue 6 (2nd November 2022) - Jorissen, Winde; Annemans, Lieven; Louis, Nicolas; Nilsson, Andreas; Willis, Michael
ABSTRACT: Objectives: The Canagliflozin and Renal Events in Diabetes with Established Nephropathy Clinical Evaluation (CREDENCE) trial showed reduced renal and cardiovascular (CV) events in patients with type 2 diabetes (T2D) and diabetic kidney disease (DKD) treated with canagliflozin 100 mg added to Standard of Care (SoC) versus SoC alone. This led to an extension of the canagliflozin 100 mg European marketing authorisation, making canagliflozin the first pharmacological therapy to receive authorisation for the treatment of DKD since the RENAAL and IDNT trials more than 20 years ago. Given the importance of cost-effectiveness analyses in health care, this study aimed to leverage the CREDENCE trial outcomes to estimate the cost-effectiveness of canagliflozin 100 mg from the perspective of the Belgian healthcare system. Methods: A microsimulation model (CREDENCE Economic Model of DKD), developed using patient-level CREDENCE trial data, was leveraged to model the progression of DKD and CV outcomes, associated costs, and life quality. Unit costs and quality-adjusted life years (QALYs) were sourced from the literature. The time horizon was 10 years and sensitivity analyses were performed. Results: Canagliflozin was associated with sizable gains in life-years and QALYs over 10 years, and the incremental cost-effectiveness ratio cost offsets associated with reductions in CV and renal complications resulted in overall net cost savings from the perspective of the Belgian healthcare system. Conclusion: Model-based results suggest that adding canagliflozin 100 mg to SoC can improve outcomes for patients with DKD while reducing overall net costs for the Belgian healthcare system. Graphical Abstract: uf0001